(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The urban growth of Quevedo has evolved rapidly due to population growth, economic development, and land-use changes. This study analyzed this expansion using geospatial modeling, identifying growth patterns and projecting scenarios through 2030. A methodology based on Markov Chains and IDRISI software was used, integrating geospatial and temporal data obtained from satellite images, official cartography, and socioeconomic records. The application of Geographic Information Systems (GIS) allowed the identification of areas with the greatest potential for urbanization, considering factors such as land use, proximity to road infrastructure, and population density. The results showed sustained urban growth, with a 32% increase (1,104 ha) in the projected urban area by 2030. At the same time, a 44.9% reduction in agricultural areas (6,040.4 ha) and a 45.0% reduction in livestock areas (1,360.9 ha) were recorded, which could generate land-use conflicts and pressure on natural resources. Furthermore, uncontrolled urban expansion was identified as a risk to equitable access to basic services, infrastructure, and security. It was concluded that it is essential to implement sustainable land-use planning strategies that regulate expansion and balance urban growth with environmental conservation and soil productivity. The development of controlled expansion plans that prioritize the provision of basic services and the protection of strategic agricultural areas, guaranteeing planned and sustainable urban development, is recommended